Effect of an occlusal splint on sleep bruxism in children in a pilot study with a short-term follow up - Giannasi, Lilian Chrystiane [UNESP]; Santos, Israel Reis; Alfaya, Thays Almeida; Bussadori, Sandra Kalil; Franco de Oliveira, Luis Vicente (Elsevier B. V., 2013)
The aim of the present study was to evaluate the effect of the use of an occlusal splint in children with bruxism in a pilot study with a short-term follow up. Seventeen children were recruited, only nine of whom formed the sample following the application of the inclusion criteria: presence of sleep bruxism for at least six months (based on parents' reports); presence of at least the first permanent molars; and no previous history of treatment involving an occlusal splint. The sample was submitted to a clinical exam. Other sleep problems were screened with the use of a sleep questionnaire filled out by parents before and after 90 days of occlusal splint usage. The children received a flat acrylic resin splint with full coverage of the occlusal surfaces to be worn in the maxilla. In children with erupting teeth, a space was created in the splint to allow normal eruption. After the 90-day period, the absence of sleep bruxism and sleep movements was noted in most of children. Moreover, snoring was reduced in nearly 50%, which raises a new issue to be investigated with regard to the pathophysiology of sleep bruxism. The use of an occlusal splint was effective in reducing the symptoms of sleep bruxism and other sleep problems. Further investigations should be carried out on the relationship between snoring and sleep bruxism in children.
Keywords: Child; Sleep apnea; Sleep bruxism; Snoring